Sulatan sa panahon ng pandemya - Barrios, Joi; Paterno, Mailin; (Merlinda Carullo) Bobis, Merlinda C. (Gantala Press, Inc., 2022)
Correspondence among Filipino women residing in the Philippines and foreign countries during the pandemic of COVID-19.